2013
DOI: 10.1136/bmjqs-2012-001372
|View full text |Cite
|
Sign up to set email alerts
|

Estimated nursing workload for the implementation of ventilator bundles

Abstract: Our estimates may serve as potentially important inputs for cost-effectiveness and decision analyses related to intensive care unit prevention activities. Further research should include direct observations about nursing time allocation related to prevention activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The taxonomy used to select the interventions is not homogeneous and seems not to reflect current ICU practices which should be based on care bundles (Branch‐Elliman et al . ) aimed at increasing patient safety and care effectiveness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomy used to select the interventions is not homogeneous and seems not to reflect current ICU practices which should be based on care bundles (Branch‐Elliman et al . ) aimed at increasing patient safety and care effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Several interventions have also changed over the years, bearing in mind that care bundles have been implemented largely in daily practice (Branch‐Elliman et al . ) and those interventions considered complex or requiring particular attention around 20 years ago have been revised or reconsidered for their capability to affect nursing time required by patients (e.g. hourly urine output check).…”
Section: Discussionmentioning
confidence: 99%
“…Offering adequate nursing hours of care during all ICU stays proved to be necessary to prevent VAP, since the study demonstrates that nurses estimated that the standard ventilator bundle requires a median of 115 min per patient per day, although the majority of nurses did not perceive that other patient care tasks were delayed. [33] The publics, federatives and Brazilian hospitals following the legislation to scale the nursing professionals, following in the ratio of two patients to each professional. Even knowing the workload or scientific evidences that demonstrate improvement in patient outcomes by providing better healthcare (in the case studied here offer more professionals to care from patients), public institutions are unable to change this situation (two patients to each nursing professional).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of time available is a central aspect in nursing, due to nursing shortages in recent years (Aiken et al, 2001;Isfort et al, 2011). The amount of time taken up by other nursing activities has been reported too (Myny et al, 2010;Branch-Elliman et al, 2013). In Germany Isfort et al (2011), conducted a survey on 532 of 2075 ICUs (Engel et al, 2007) and found that the number of nursing staff has decreased by 13% over the last 15 years, while admission rates increased by 12% and workload has increased as a consequence.…”
Section: Discussionmentioning
confidence: 99%